SPECIFICS OF PEDIATRIC INJURIES ASSOCIATED WITH THE USE OF PERSONAL ELECTRIC MOBILITY DEVICES - Ю. Коцюбинська; Н. Козань; В. Чадюк; Т. Котик; І. Іваськевич; А. Коцюбинський (Неонатологія, хірургія та перинатальна медицина, 2025)
Injuries among children resulting from the use of personal electric mobility devices are common and contribute to a range of adverse societal outcomes, including increased financial strain on healthcare systems, instances of disability, pediatric mortality, and other related consequences. Consequently, investigating the characteristics of pediatric injuries associated with this type of trauma is of paramount importance, as the findings may serve as a foundation for the development and implementation of preventive strategies.